2005
DOI: 10.1021/jm0507781
|View full text |Cite
|
Sign up to set email alerts
|

2-[3-[2-[(2S)-2-Cyano-1-pyrrolidinyl]-2-oxoethylamino]-3-methyl-1-oxobutyl]- 1,2,3,4-tetrahydroisoquinoline:  A Potent, Selective, and Orally Bioavailable Dipeptide-Derived Inhibitor of Dipeptidyl Peptidase IV

Abstract: Dipeptidyl peptidase IV (DPP-IV) inhibitors are expected to become a new type of antidiabetic drugs. Most known DPP-IV inhibitors often resemble the dipeptide cleavage products, with a proline mimic at the P1 site. As off-target inhibitions of DPP8 and/or DPP9 have shown profound toxicities in the in vivo studies, it is important to develop selective DPP-IV inhibitors for clinical usage. To achieve this, a new class of 2-[3-[[2-[(2S)-2-cyano-1-pyrrolidinyl]-2-oxoethyl]amino]-1-oxopropyl]-based DPP-IV inhibitor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
9
0

Year Published

2006
2006
2021
2021

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 26 publications
(9 citation statements)
references
References 44 publications
0
9
0
Order By: Relevance
“…Other examples of enzyme targets for adamantane-based pharmaceuticals are soluble epoxide hydrolases, 51,52 protein phosphatase 2A, 53 or the hydroxysteroid dehydrogenases. 5456 The various enzymes targeted by functionalized adamantane-based pharmaceuticals demonstrate the trend towards an utilization of the adamantane scaffold to orientate (co)pharmacophors to positions beneficial for enhanced interaction with the target's active site. We will conclude this chapter with an antibiotic natural product modified with an adamantane core, 57 re-iterating the concept of natural-product inspired pharmaceuticals.…”
Section: Introductionmentioning
confidence: 99%
“…Other examples of enzyme targets for adamantane-based pharmaceuticals are soluble epoxide hydrolases, 51,52 protein phosphatase 2A, 53 or the hydroxysteroid dehydrogenases. 5456 The various enzymes targeted by functionalized adamantane-based pharmaceuticals demonstrate the trend towards an utilization of the adamantane scaffold to orientate (co)pharmacophors to positions beneficial for enhanced interaction with the target's active site. We will conclude this chapter with an antibiotic natural product modified with an adamantane core, 57 re-iterating the concept of natural-product inspired pharmaceuticals.…”
Section: Introductionmentioning
confidence: 99%
“…The SureChemOpen entry, via a same-connectivity link (SID 157613372) established a link to example 61 in a Kenkyusho patent, WO2004067509 [19]. The ChEMBL entry (SID 103476839) was linked to a publication (PMID 16392822) where the IC50 inhibitory activity of this structure against DPPIV was 49 nM [20]. We also used CID 10383508 to answer the question “what additional connections can be made for a structure using similarity searches?” in two ways.…”
Section: Resultsmentioning
confidence: 99%
“…Very recently, Jiaang and co-workers reported that prolinenitrile-based inhibitors with heterocyclic rings showed high selectivity and potency for DPP-IV as well as in vivo efficacy compared to vildagliptin [14]. We had also pursued the possibility of isoindoline class DDP-IV inhibitors and found their high potency and excellent in vivo efficacy [15].…”
Section: Resultsmentioning
confidence: 99%